2019
DOI: 10.1016/j.mex.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cell RNA characterisation from colorectal cancer patient blood after inertial microfluidic enrichment

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Douard et al, showed that the expression of carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5; formerly CEA)102,115 and CEACAM7 (formerly CGM2)115,116 was more sensitive than use of a single marker in detecting CTCs, in contrast to the other studies, Bessa et al, showed that assessment of CTCs using RT-PCR CEA before surgery does not have prognostic value for CRC patients 117…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Douard et al, showed that the expression of carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5; formerly CEA)102,115 and CEACAM7 (formerly CGM2)115,116 was more sensitive than use of a single marker in detecting CTCs, in contrast to the other studies, Bessa et al, showed that assessment of CTCs using RT-PCR CEA before surgery does not have prognostic value for CRC patients 117…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies emphasized only on CEA as a marker (five articles)87–91 and several studies also introduced both CK20 and CEA as prognostic markers 9296. In most articles, CK20 and/or CEA were accompanied by markers such as CK19,97102 GCC,96,103,104 Prominin 1 (CD133),95,100,105,106 EPCAM,107–109 survivin,110,111 ProtM,112 mucin 1 (MUC 1),105 and mucin 2 (MUC 2),99 and telomerase reverse transcriptase (hTERT) 101,113,114…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes of three CTCs from a single patient were quite heterogeneous, as only ~5% of mutations were shared between two CTCs, and 2% were shared by all three. Winter et al validated an integrated protocol to probe colorectal cancer CTC RNA for tumor marker discovery using a slanted spiral microchannel for cell enrichment followed by ddPCR for detecting colorectal cancer genes within enriched CTC samples [ 65 ]. Consistent mutations between collected CTCs processed with these methods may reveal new biomarkers relevant to tumorigenesis and metastasis.…”
Section: Endogenous Targetsmentioning
confidence: 99%
“…Five traps were shown with higher magnification for better illustration of the single and double occupied traps. No cell was found to stick to the main channel, inlet and outlet of the device CTC isolation post enrichment from peripheral blood, based on previously published works of our research group [28][29][30][31]. First, the harvested cells were stained using DAPI, anticytokeratin and CD-45 and then a mixture of both cell types was made at the optimum concentration.…”
Section: Device Performance-trappingmentioning
confidence: 99%